Caracterización geoeléctrica de los depósitos superficiales en la Antártida Occidental (Isla Livingstone, Islas Shetland del Sur, Antártida Occidental) - Muñoz Martín, Alfonso; Giner Robles, Jorge; González Casado, José Manuel; López Martínez, Jerónimo; Durán Valsero, Juan José; Gumiel, Pablo; Serrano, Enrique (Sociedad Geológica de España, 2000)
The geophysical study of superficial deposits (mainly gravels) in ice-free areas near the seashore in the South Shetland Islands (Antarctica) allows establishing the possible existence of permafrost and buried ice bodies. In this work we have investigated the internal structure of Quaternary sediments using the resistivity method (vertical electric sounding, V.E.S.), with the purpose of establishing the resistivity values of the different materials and their geometry. We present here the results obtained from 17 vertical electric soundings carried out in Caleta Española, (north coast of Hurd Peninsula), and in the surroundings of Caleta del Glaciar Rocoso (south coast of Hurd Peninsula), both in Livingston Island. Vertical electric soundings interpretation has allowed us to characterise different units from the resistivity values (active layer, permafrost, buried ice, Quaternary deposits and their basement), and to establish the inter-phase between sea water and continental water. Moreover, with the resistivity method we have deduced the spatial distribution of some of these beds. In this way the permafrost (with resistivity values ranging between 13000 and 35000 Ω*m), and the associated active layer, is restrained to shallow depths(< 2 m) and located in the surveyed areas faraway from the seaside (i.e. mainly in the upper raised beaches). Buried ice under coarse Quaternary deposits have resistivity values of one major order magnitude than the permafrost (> 60000 Ω *m) and has been only found in the studied rock glacier.